(untitled) (Comprehensive Journal of Science, 2026)
This study examines the impact of applying corporate governance principles on combating financial corruption in Libyan commercial banks, from the perspective of the Audit Bureau as a supervisory authority responsible for monitoring and evaluating financial and administrative performance. The study adopts a descriptive-analytical approach and relies on an electronic questionnaire as the main data collection tool, targeting a sample of 65 employees from the Audit Bureau specialized in banking oversight. The results indicate that the majority of participants hold a bachelor’s degree, with most having short to medium professional experience, reflecting a relatively recent practical understanding of supervisory work. The findings also show that the overall level of corporate governance implementation in commercial banks is generally good. Financial transparency ranked as the most applied dimension, followed by accountability, then fairness and equality, while the independence of boards of directors ranked last with a relatively weak level of application. Regarding the role of the Audit Bureau, the results reveal that it plays an effective supervisory role, particularly in preparing reference reports and documenting recurring observations. However, there is a need to strengthen direct monitoring mechanisms to better detect financial corruption. The study also finds a strong inverse relationship between corporate governance and financial corruption, indicating that weak governance—especially the absence of transparency—leads to increased financial manipulation and corruption. Furthermore, the findings demonstrate that the organizational and financial/accounting dimensions of governance have a greater impact on reducing corruption compared to behavioral dimensions. The study also highlights the importance of continuous training, strengthening the legal framework, and reducing political interference as key factors in enhancing governance effectiveness. Based on these findings, the study recommends enhancing transparency and accountability, improving board independence, developing employees’ capacities, and strengthening the Audit Bureau’s proactive oversight role, in order to improve institutional performance and reduce financial corruption in the banking sector.